GAMBARAN LITERASI KESEHATAN MENTAL MALUKU UTARA BERDASARKAN JENIS KELAMIN USIA TINGKAT PENDIDIKAN KABUPATEN KOTA - Amalia S.J Kahar; Husnul Hasanah N. Saleh (Universitas Muhammadiyah Gresik, 2024)
Background: In 2021, the Central Statistics Agency determined that North Maluku province was the province with the highest happiness index in Indonesia, however problems related to mental health continued to increase every year. The increase in mental health problems is also influenced by the lack of public literacy on mental health. Objective: The aim of this research is to determine the mental health literacy picture of the people of North Maluku in terms of gender, age, education level and district/city. Method: The study used quantitative research methods with the type of research testing differences using Mental Health Literacy (MHL) measuring instruments. The data analysis technique is the ANOVA difference test using the SPSS 19 application. Resuts: the results of the study showed that mental health literacy in North Maluku Province in the moderate category was 63.13%, the low category was 10.62% and the high category was 26.25%. There are no differences in mental health literacy by gender, meanwhile there are significant differences in mental health literacy levels based on age, education level and district or city. Conclusion: The conclusion of the study is the majority of people have fairly good mental health literacy in North Maluku Province.